Οἰκονομικὸς καὶ κοινωνικὸς ρόλος τῶν ἑλληνορθόδοξων κοινοτήτων τῆς Πόλης: μιά πρόταση γιὰ τὴν ἐρευνητικὴ ἀξιοποίηση τῶν ἀρχειακῶν τεκμηρίων τῆς ζωῆς τῶν Ρωμιῶν τῆς Πόλης - ΚΑΝΝΕΡ ΕΦΗ (Μνήμων, 2011)
The Program of the Detection, Recording, Microfilm Depiction and Digitalizationof the Istanbul Greek-orthodox Community Archives was initiated in1995. Whereas in its initial phase several institutions were involved in it, from1998 on the Faculty of Philosophy and History of Science of the Athens Universityremained solely responsible for the Program. The Program researchersvisited 38 out of 42 Rum Istanbul communities, recorded all parochial andcommunal archives and photographed more than 1.000.000 pages of them.They also formed a digital library out of the 1/3 of this material. This libraryis a part of the Historical Archives Electronic Processing Laboratory of theFaculty of Philosophy and History of Science.This material depicts the whole spectrum of activities and everyday life inthe Istanbul Rum communities and parishes from the last 18th century decadesto the 1990s. It permits us to understand the place of the community and parishin Istanbul Rum’s lives throughout the years. In this purpose we proposea research program entitled Economic and Social Role of the Istanbul GreekorthodoxCommunities and including the following aspects:• Mechanisms of institutionalization and representation in parishes andcommunities• Parishes’ and communities’ funds• Poverty: discourses and practices around it• Community salaried staff• School education in communities and parishes• Religiosity among the Istanbul Greek- Orthodox populations from thelate Ottoman period to our days.• Family strategies in Istanbul Orthodox communities